Efforts to Improve Collaboration Skills and Student Learning Outcomes Using the Teams Games Tournament Model - Nur Ihwanto; Herita Warni; mashud mashud (Universitas Suryakancana, 2022)
This study aims to determine whether the application of the Teams Games Tournament (TGT) learning model can improve collaboration skills and student learning outcomes in the basic motion combination material of walking, running, jumping, and throwing in class V.A. students at SDN 2 Loktabat Selatan. In this study, we used the class action research method (classroom action research) with the Kemmis and Taggart models (planning, implementing actions, observing, and reflecting). The subjects of the study were 14 students in class V.A. at SDN 2 Loktabat Selatan. Data collection instruments were tests (multiple choice) and non-tests (observations). The overall data is in the form of quantitative data, which is then analyzed descriptively using the percentage formula. The results showed an increase in collaboration skills and student learning outcomes from pre-cycle to cycle I. The value of pre-cycle collaboration skills increased by 37%, then increased by 93% in cycle I; the value of pre-cycle cognitive skills increased by 50%, then increased by 93% in cycle I; and the value of pre-cycle psychomotor skills increased by 100%. It can be concluded that by applying the Teams Games Tournament learning model, it can improve the collaboration skills and learning outcomes of students in class V.A. SDN 2 Loktabat Selatan through the combination of basic motions of walking, running, jumping, and throwing..Key words: Collaboration Skills, Learning Outcomes, Teams Games Tournament